ANALISIS KUALITAS INSTRUMEN ASESMEN SOAL SAINS BERBASIS STEM BERORIENTASI PISA PADA SISWA KELAS X SMA NEGERI 1 SEMARAPURA - I Made Subrata; I Gusti Ayu Rai; Ni Luh Putu Tejawati (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to analyze the characteristics and quality of a STEM-based science assessment instrument oriented toward the Programme for International Student Assessment (PSA) for tenth-grade students at SMA Negeri 1 Semarapura. This study used a mixed methods approach with a sequential explanatory design that integrates qualitative and quantitative analysis. The subjects were tenth-grade students in the 2025/2026 academic year. Qualitative data were collected through observation, interviews, and document studies to assess the suitability of the instrument's characteristics to the PISA scientific literacy framework, which includes aspects of context, content, and competency. Quantitative data were obtained through instrument trials to analyze item quality, including validity, reliability, difficulty level, and discriminatory power. The results showed that the developed instrument met the PISA assessment characteristics by incorporating real-world contexts, integration across STEM disciplines, and higher-order thinking skills. Quantitatively, most items had good validity, high reliability, moderate difficulty level, and adequate to good discriminatory power. However, some items needed revision to improve the instrument's quality. Thus, the developed assessment instrument is suitable for measuring students' scientific literacy and supporting the development of STEM-based assessments oriented towards international standards.